Innovator Intelligent Air Conditioner System: Marketing Plan And Pricing Strategy - Ching, Yee Khim (2009)
A research has been carried out to determine the acceptable price for ICONS. if the selling price influences the purchase decision. whether e-marketing program is preferable to the ordinary marketing program and the potential of air conditioner sales is in the increase for the next six to twelve months. Satu penyelidikan telah dijalankan untuk memastikan sasaran harga bagi ICONS, sama ada keputusan pembelian XIV ditentukan oleh harga barang, sama ada atur cara e-pasaran lebih sesuai berbanding dengan atur cara pasaran biasa dan sama ada j ualan bagi penyaman sej uk udara akan meningkat dalam jangka masa enam hingga dua belas bulan